Maternity colonies of Myotis brandtii in the Polesie State Radiation-Ecological Reserve - Dombrovski, V.C. (Theriologia Ukrainica, 2018)
Two lactating females of Brandt’s bat were radio-tracked during 26–28 June 2016 and 14–20 June 2017 in the Polesie State Radiation-Ecological Reserve (Khoiniki district, Gomel region). Four tree roosts of nursery colonies of Brandt’s bat were found. The roosts were detected at the dead oak trees in an old oak forest at a distance of 142–870 m from each other. Roosts were located in trunk cracks and behind peeling bark at a height of 4–16 m above the ground. Visual inspection during the evening revealed that the maternity colony consisted of 8–10 individuals of Brandt’s bat. In 2016, there was a mixed colony of Brandt’s bat and the soprano pipistrelle (Pipistrellus pygmaeus). This is the first documented record of maternity colonies of Brandt’s bat and the easternmost finding localities of this species in Belarus. За допомогою радіостеження за двома репродуктивно активними самками нічниці північної протягом 26–28 червня 2016 р. та 14–20 червня 2017 р. в Хойницькому районі Гомельської обл. на території Поліського державного радіаційно-екологічного заповідника виявлено 4 денних сховища даного виду. Вони розташовувалися в сухостійних дубах на висоті 4–16 м у старовіковій розрідженій діброві на відстані 142–870 м один від одного. Візуальним оглядом встановлено, що у 2016 р. колонія налічувала 10 особин нічниці північної та 20–30 особин нетопира пігмея (Pipistrellus pygmaeus), у 2017 р. — 8 особин нічниці північної. Це перші документовані знахідки материнських колоній нічниці північної та найсхідніші з відомих для Білорусі точки реєстрації виду.